(untitled) - Yu, Peter Y (New York, 2010)
Excellent bridge between general solid-state physics textbook and research articles packed with providing detailed explanations of the electronic, vibrational, transport, and optical properties of semiconductors
Vật lý bán dẫn
Keywords: Semiconductors,Chất bán dẫn; Materials.,Vật liệu.